STUDI PENAMBAHAN STRUKTUR BETON BERTULANG MENJADI KOMPOSIT DENGAN BAJA BERGELOMBANG PADA OVERPASS PUCUNG LOR KROYA - Raden Aufa Dhia Anggara; Ashar Saputra (TEKNISIA, 2021)
The construction of a nonlevel railway crossing in Pucung Lor Kroya was aimed to improve safety and smooth traffic between railways and roads. Increasing frequency of railways through the Double Track Railway Project of South Java demands a fast pace construction of railway crossing without disrupting any railway traffic. So, the overpass structure will be built using Corrugated Mortar Busa Pusjatan (CMP) technology with Corrugated Steel Plate (CSP) on a curve structure 1 (P1) with a 25-meter span and curve structure 2 (P2) with a 12-meters span. When construction began, planners added reinforced concrete layers until composite with CSP to increase structural capacity and became structural protectors if CSP yielded or corrosions. Overpass modeling was done using MIDAS Civil 2019 based on finite element 3D to check strength capacity and service limits. The addition of reinforced concrete structures to composites with CSP is also compared to the non-composite design of CMP Pusjatan to see the effect on internal forces, stress, and deflection of CSP although the stress on foam mortar. Based on the results, the composite design overpass analysis satisfies compression-bending and shearing capacity checks based on Ultimate Limit States (ULS-PBKT) and service limit based on Serviceability Limit State (SLS-PBL). The addition of reinforced concrete to composite with CSP increases safety factor value because CSP stresses are lower than non-composite designs. The potential collapses from foam mortar can also be reduced as the structure becomes rigid.